Kualitas selai lembaran ekstrak ubi jalar ungu dengan penambahan pasta ekstrak kulit nanas madu - Gisela Cita Tarudea; Yuliana Reni Swasti; Franciscus Sinung Pranata (AGROINTEK, 2026)
Fruit leather is a semi-moist food product that has a distinctive fruit flavour and a compact texture, which is not easily broken, and can be rolled up. Using purple sweet potatoes, rich in dietary fibre, can help increase the fibre content in fruit leather products. Pineapple is a commonly found fruit in Indonesia; pineapple peel is used as a by-product that is seldom used and is only thrown away; it has the potential to be a source of pectin. This study was conducted to determine the chemical, physical, microbiological, and organoleptic quality of fruit leather with the use of purple sweet potato extract with the addition of honey pineapple peel extract paste, as well as to determine the best comparison between purple sweet potato extract and honey pineapple peel extract paste. This study was conducted using the CRD method with variations of purple sweet potato extract and honey pineapple peel extract paste variations as follows: 70:0 (K), 70:3 (A), 70:6 (B), and 70:9 (C). This study showed that the use of purple sweet potato extract and honey pineapple peel extract paste had a significant effect on moisture content, ash content, insoluble fibre content, soluble fibre content, dissolved solids, texture, colour, and organoleptic properties. The fruit leather made in this study has met the TPC and Yeast Mould Count standards regulated by the National Standardisation Agency (2008). Fruit leather with the best quality results from this study is purple sweet potato extract fruit leather with the addition of honey pineapple peel extract paste at 70:9%.